Analysis of Transport Accessibility and Factors Influencing The Competitiveness of The Ports of Świnoujście and Gdynia - Dariusz KLOSKOWSKI; Weronika ZIMNY; Vladyslav LIASHUK (Communications of International Proceedings, 2024)
This study deals with the transport accessibility of the main ports in Poland, which affect the state of the national economy in the statutory sense. The seaports: Świnoujście and Gdynia, acting as the main communication hubs in multimodal transport, are at the same time an important element in global supply chains - they are also strategic points for transshipment of goods and passenger service, combining various branches of transport, including sea, land and rail. The article presents a comparative analysis of the seaports in Świnoujście and Gdynia, focusing on their transport accessibility and competitiveness in the logistics market. Key aspects, such as the length of the quay, the number of ships served and the volume of container transshipment, are taken into account to ensure a comprehensive result of each port in the context of operational attractiveness. There are many examples of presenting transport accessibility in the literature on the subject, and many examples are also contained in the literature on the ports themselves. However, in the study, the research was focused on a comparative analysis of the ports themselves as poles in opposing markets in geographical terms. In this paper, regression analysis was used to assess the extent to which infrastructure, ship accommodation capacity and container handling capabilities affect the port’s turnover and importance in international supply chains. The results, determined based on literature review, source data and analyses, indicate that the Port of Gdynia, with its well-developed infrastructure and capacity to handle larger container transshipments, plays a key role as a competitive and accessible port. Although the Port of Świnoujście uses significant berthing resources, it also shows lower efficiency in container handling and ship transshipment, which suggests that its potential can be better utilized through further investments in infrastructure and transshipment logistics. The conclusions drawn from the analysis emphasize the importance of development strategies focused on the optimization of infrastructure and transport accessibility, which are the basis for strengthening the competitive position of ports in the region.
Keywords: transport accessibility; port competitiveness; seaport